PENGARUH PENGETAHUAN PERPAJAKAN, KUALITAS PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA BEKASI - Ismi Azhari Karima (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to analyze the factors influencing tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City. MSMEs play a significant role in Indonesia's economy, but their tax compliance level remains relatively low. Several factors are suspected to be the causes, including a lack of understanding of tax regulations, suboptimal tax services, and less strict tax penalties. Through a quantitative approach using surveys, this study attempts to identify the dominant factors affecting MSMEs' tax compliance in Bekasi City. The research results are expected to provide effective policy recommendations for the government and other stakeholders to improve MSMEs' tax compliance and support sustainable economic growth..